Production and characterization of AlCuMgMnZn high entropy alloy prepared by hot pressing - Sezer, Rasit; Erol, Mahmut; Bayrak, Yahya; Kisasoz, Alptekin (ELSEVIER SCIENCE SA, 2026)
High entropy alloys attracted attention owing to enhanced microstructural, mechanical and corrosion properties. In this study, AlCuMgMnZn alloys were produced by the hot pressing at various temperatures and duration. Microstructure, wear and corrosion properties of the produced alloys were investigated. The samples were produced at 500 degrees C, 550 degrees C, and 600 degrees C for 30 min and 60 min. The samples consisted of copper based matrix, intermetallics and complex phases such as MgZn2, Mg2Zn11, MgCuZn, and AlCuMg. As the production temperature increased, complex intermetallic phases as well as the manganese based phase were formed. The wear rate decreased from 8.745 & sdot;10-5 mm3/Nm to 7.785 & sdot;10-5 mm3/Nm via hot pressing process at 600 degrees C for 60 min. The formation of the manganese based phases and intermetallic structures improved wear behavior of the AlCuMgMnZn high entropy alloy. The samples produced at 600 degrees C exhibited significantly improved corrosion behavior. This phenomenon was attributed to microstructural transformations and the formation of a denser, less porous structure. As a result, the samples produced at high hot pressing temperatures exhibited significantly improved properties in terms of both corrosion and wear resistance.
Keywords: High entropy alloys; AlCuMgMnZn; Wear; Corrosion; Electrical conductivity; SOLID-SOLUTION PHASE; MECHANICAL-PROPERTIES; MICROSTRUCTURE; TEMPERATURE; STABILITY; COATINGS; MG; Materials Science